2015
DOI: 10.3109/02699052.2015.1037349
|View full text |Cite
|
Sign up to set email alerts
|

S100B protein as a screening tool for computed tomography findings after mild traumatic brain injury: Systematic review and meta-analysis

Abstract: After MTBI, serum S100B protein levels are significantly associated with the presence of intracranial lesions on CT scan. Measuring the protein could be useful in screening high risk MTBI patients and decreasing unnecessary CT examinations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
21
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(22 citation statements)
references
References 104 publications
1
21
0
Order By: Relevance
“…The results of our study expand and corroborate those from previous systematic reviews and meta-analyses, [62][63][64] and confirm that the implementation of S100B might allow a reduction of the number of CT scans by *30%. 3 These considerations also have broad financial implications for healthcare costs.…”
supporting
confidence: 89%
“…The results of our study expand and corroborate those from previous systematic reviews and meta-analyses, [62][63][64] and confirm that the implementation of S100B might allow a reduction of the number of CT scans by *30%. 3 These considerations also have broad financial implications for healthcare costs.…”
supporting
confidence: 89%
“…For example, the meta‐analysis for the marker ubiquitin carboxy‐terminal hydrolase L1 (UCHL‐1) recently published, stated that in studies with a total of 1,138 TBI cases and 1,373 controls there was a significant increase in serum UCH‐L1 levels in patients with TBI compared to controls (weighted mean difference 0.96, 95% confidence interval [CI] 0.31–1.61; p = 0.004) . Two independent meta‐analyses for S100B in TBI concluded that “Low serum S100B levels accurately predict normal CT findings after mTBI and that S100B sampling within 3 h of injury should be considered when no focal neurological deficit, or significant extracerebral injury is present.” These studies recommend a cut‐off for omitting CT set at <0.10 ng/ml . There is therefore an opportunity to produce a test with high negative predictive value as a point‐of‐care device so that many unnecessary scans can be avoided, and separately, a laboratory‐based positive predictive value test to diagnose complications after TBI.…”
Section: Blood–brain Barriermentioning
confidence: 99%
“…Many groups have described this variability, and most of the data presented so far has focused on the astrocytic protein S100B [8]. This biomarker has been studied for several years, and investigated as a tool to diagnose non-CNS conditions, mainly malignant melanoma [9].…”
Section: Introductionmentioning
confidence: 99%